2015
DOI: 10.1109/tps.2015.2448660
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Permeabilization Studies of <italic>Chlorella</italic> sp. by Pulsed Electric Fields

Abstract: Microalgae cell membrane permeabilization has been studied, for Chlorella sp., in a continuous 6-L prototype for different field strengths in order to minimize the specific energy supplied and the treatment time. Regarding lower electrical field strength values, the optimal results were achieved at 10 kV/cm, 200 Hz, and 5-µs per pulse, corresponding to an energy delivered of 9 kJ/kg of culture, with 97% of cells affected after 300 ms of treatment time. Regarding energy delivered per kilogram of Biomass, the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The presented experimental results indicate that a minimum specific energy input of 19.6 kJ kg −1 is necessary to perforate 100% of the cells in electroporation cuvettes. These results are in good agreement with the work of Rego et al (2015), who treated Chlorella cells in a continuous treatment chamber with a parallel plate electrode configuration. According to their results, about 20 kJ kg −1 were necessary for permeabilizing 100% of the treated cells.…”
Section: Discussion Of Kinetic Modeling and Numerical Simulation As Tsupporting
confidence: 91%
See 1 more Smart Citation
“…The presented experimental results indicate that a minimum specific energy input of 19.6 kJ kg −1 is necessary to perforate 100% of the cells in electroporation cuvettes. These results are in good agreement with the work of Rego et al (2015), who treated Chlorella cells in a continuous treatment chamber with a parallel plate electrode configuration. According to their results, about 20 kJ kg −1 were necessary for permeabilizing 100% of the treated cells.…”
Section: Discussion Of Kinetic Modeling and Numerical Simulation As Tsupporting
confidence: 91%
“…Fourth, it should be mentioned that the model calibration was done at a dry mass content of 1 g l −1 . Nevertheless, it was shown that the PEF treatment of microalgae is independent of the biomass concentration up to concentrations 160 g l −1 for Auxenochlorella protothecoides (Goettel et al, 2013) and 40 g l −1 for Chlorella vulgaris (Rego et al, 2015) (higher concentrations were not tested in the cited papers). Based on these results, the validity of the proposed model at higher biomass concentrations seems likely, although it should be proved in future work.…”
Section: Discussion Of Kinetic Modeling and Numerical Simulation As Tmentioning
confidence: 99%
“…Yet, an enzymatic disruption could not increase chlorophyll release in C. vulgaris biomass [ 61 ]. Similarly, a mechanical disruption treatment was unnecessary when chlorophyll bio-accessibility was considered in C. vulgaris biomass, with bio-accessibility values already ranging between 77–84% for untreated biomass [ 62 ]. No literature was found on fatty acid release during C. vulgaris digestion.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to increasing yield, PEF allows to eliminate removing the water stage for fresh water algae. The working principle of the PEF was explained as cell membrane electropermeabilization or electroporation by electromechanical compression and electric field-induced tension in many studies (Luengo et al, 2014;Rego et al, 2015;Parniakov et al, 2015;Eing et al, 2013;Zbinden et al, 2013). Electroporation results in an increase in permeability of cell membrane to ions and macromolecules because of local defects or pores in the cell membrane (Parniakov et al, 2015).…”
Section: Pulsed Electric Field (Pef)mentioning
confidence: 99%